2011
DOI: 10.1111/j.1601-5037.2011.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of gingival inflammation in orthodontic patients with ozonated water irrigation - a pilot study

Abstract: A single subgingival irrigation of 0.01 mg l(-1) ozonated water can effectively reduce the gingival inflammation in orthodontic patients, which is also reflected in the reduction of LDH enzyme levels. However, further randomized controlled trials are required to validate the use of ozone irrigation in orthodontic patients for plaque control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
(42 reference statements)
2
22
0
5
Order By: Relevance
“…Our results are in accordance with those of other clinical trials that did not show statistically significant differences in PI, GI, probing pocket depth and clinical attachment loss following the addition of ozonated water irrigation to SRP, taking into consideration that none of the previous studies used distilled water irrigation in the control . However, better clinical results have been shown when using ozone irrigation in patients with aggressive periodontitis .…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in accordance with those of other clinical trials that did not show statistically significant differences in PI, GI, probing pocket depth and clinical attachment loss following the addition of ozonated water irrigation to SRP, taking into consideration that none of the previous studies used distilled water irrigation in the control . However, better clinical results have been shown when using ozone irrigation in patients with aggressive periodontitis .…”
Section: Discussionsupporting
confidence: 91%
“…Ozonized water subgingival irrigation was used successfully in the treatment of aggressive perioodontitis [13]. In patients undergoing orthodontic treatment, use of ozonized water showed definite improvement in gingival inflammation [14]. The present study is being undertaken to evaluate the use of ozonized water subgingival irrigation as an adjunct to scaling and root planing in patients with chronic generalized periodontitis.…”
mentioning
confidence: 99%
“…The results followed an expected pattern as seen in the study conducted by Dhingra and Vandana. 11 Schlagenhauf et al 15 showed that ozonated water was highly effective in killing both Gram +ve and -ve oral microorganisms in vitro.…”
Section: < 83mentioning
confidence: 99%
“…In the field of orthodontics, ozone gas has been tested for its anticariogenic effect, for its effect on the shear bond strength of orthodontic brackets to enamel and on the presence of gingival inflammation. [9][10][11] The aim of the study was to compare the clinical effects of subgingival irrigation with ozonated water to those seen with chlorhexidine solution irrigation on gingivitis in patients with fixed orthodontic appliances and also to correlate the clinical effects with the MCP-1 activity in the GCF.…”
mentioning
confidence: 99%